Factors affecting efficiency of police stations in metropolitan police division 3 - Chaiwuttisak, Pornpimol (My University, 2019)
The objective of this research is to evaluate the relative performance efficiency and determine the factors affecting the efficiency of 11 police stations in the Metropolitan Police Division 3. The first stage is to analyze the efficiency of the police station by Data Envelopment Analysis (DEA) that measures the variable return to scale (VRS) and considering output-orientation. Input variable is the number of police officers. Output variables are the percentage of arrests with remand in custody, from the total amount of arrests, the percentage of arrests with remand in traffic offences, from the total amount of traffic offences, an average score of people’s satisfaction on facilities of the police station, operational processes and the service of the staffs. Secondary data are collected from 11 police stations during January and December 2017, for a total of one year. Primary data, which are the satisfaction score, are obtained from the sample survey. For the second stage, the factors affecting the performance efficiency of the police station are analyzed using multiple regression analysis. The efficient score calculated in the first stage is defined as the dependent variable. The results show that 4 police stations or 36% pure are technically efficient and there is only one police station (or 9%) with scale efficiency. In addition, the population density within the area responsible for the police station has affected the pure technical efficiency of the police station. The number of community resources within the area responsible for the police station has an effect on the scale efficiency of the police station.
Keywords: Data envelopment analysis; Multiple regression analysis; Police station; Pure technical efficiency; Scale efficiency